ECONOMIC TRANSFORMATION THROUGH WOMEN'S COOPERATIVES: THE ROAD FROM PROBLEMS TO SOLUTIONS (Third Sector Social Economic Review, 2025)
Women face multi-layered challenges such as unemployment, low income, informal employment and gender inequality. Women's co-operatives have the potential to provide solutions to these problems, reinforcing economic and social solidarity and enabling women's economic empowerment. The study aims to examine the impact of women's co-operatives on women's economic lives, to examine the economic problems faced by women and to evaluate the solutions provided by women's co-operatives to these problems. In this context, it focussed on the partners of the Women's Initiative Production and Business Cooperative operating in Antalya, Burdur and Isparta provinces. In order to understand the life experiences of co-operative members, a qualitative research design, phenomenology design, was used in the study. The data obtained were analysed using the content analysis method and with the help of Maxqda software According to the study, women's co-operatives in the Western Mediterranean have helped unemployed women to enter the formal economy, particularly by providing employment opportunities for women working at home. With the income generated through co-operatives, women have been able to meet their own needs and reduce poverty levels. In conclusion, women's co-operatives in the Western Mediterranean have been shown to bring about change in women's economic lives, and women's co-operatives have played an intermediary role in providing solutions to the economic problems that women face in their lives. In addition, the findings guide strategies for women's economic empowerment and provide practical recommendations for policy makers in this area.
Keywords: Women's Co-operative; Disadvantaged Group; Women's Issues; Economic Life; Economic Transformation